2021
DOI: 10.1111/cob.12476
|View full text |Cite
|
Sign up to set email alerts
|

The effect of overweight/obesity on diastolic function in children and adolescents: A meta‐analysis

Abstract: Summary Left ventricular diastolic function (LVDF) is an important marker of early cardiovascular remodelling, which has not been well summarized in young people with overweight/obesity. Weighted, random‐effects regression was used to determine the strength of associations of both body mass index (BMI) and homeostatic model assessment of insulin resistance (HOMA‐IR) with LVDF measures, adjusting for age and sex. Six databases were searched after PROSPERO registration (CRD42020177470) from inception to July 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 92 publications
3
12
0
Order By: Relevance
“…Larger patient cohorts are necessary for further investigation to validate these differences. Consistent with our findings, obesity and smoking in adolescents have been linked to increased left ventricular volume and reduced myocardial diastolic function ( 20 , 31 , 32 ). Our study also depicted the impact of BMI on cardiac function, but no significant correlation was seen between smoking and cardiac function parameters, potentially due to the limited number of smokers included in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Larger patient cohorts are necessary for further investigation to validate these differences. Consistent with our findings, obesity and smoking in adolescents have been linked to increased left ventricular volume and reduced myocardial diastolic function ( 20 , 31 , 32 ). Our study also depicted the impact of BMI on cardiac function, but no significant correlation was seen between smoking and cardiac function parameters, potentially due to the limited number of smokers included in our study.…”
Section: Discussionsupporting
confidence: 92%
“…This may be because there were only two pediatric patients with an LV mass z-score of > 2; thus, it was not a comparative evaluation of patients with LV hypertrophy and those without. A recent meta-analysis by Burden et al showed reduced diastolic dysfunction with an increased E/e' ratio and decreased E/A ratio in children with obesity [30]. This is similar to the results of our study showing that a higher BMI z-score was associated with a lower E/A z-score, and a higher TG was associated with a higher E/e' z-score.…”
Section: Discussionsupporting
confidence: 92%
“…Input from AHPs into the design and/or implementation of primary and secondary prevention strategies may contribute to reduced incidence of overweight/obesity in young children. This is of vital importance to public health given the potential development of sub‐clinical disease in children living with overweight and/or obesity 7,8 . In addition, obesity may also track into adulthood and lead to the development of clinical disease such as type 2 diabetes 10–12 …”
Section: Discussionmentioning
confidence: 99%
“…This is of vital importance to public health given the potential development of sub-clinical disease in children living with overweight and/or obesity. 7,8 In addition, obesity may also track into adulthood and lead to the development of clinical disease such as type 2 diabetes. 10-12…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation